The significance of endothelium diagnostics in women at menopausal period - Owczarek, Danuta; Stachowiak, Grzegorz; Połać, Ireneusz; Pertyński, Tomasz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
Vascular wall, and endothelium in particular, plays an important role in haemostasia. Endothelial cells produce a number of various compounds influencing both vascular muscle tone and coagulation and fibrinolysis processes. Endothelial cells lesion is related to cardiovascular diseases. Endothelial diagnostics is of particular importance in menopausal women exhibiting the presence of many coexisting risk factors for coronary heart disease and venous thromboembolism. Administration of hormone replacement therapy during this period is a next reason to pay attention to the endothelial cells status.